Polyisoprenoid Distribution in Stems and Leaves of Pinus Merkusii Strains - Nur Indah Lestari; Rizka Amelia; Mohammad Basyuni (Science and Technology Indonesia, 2021)
Living things produce secondary metabolites, one of which is abundant in plants, namely polyisoprenoid alcohol compounds. Polyisoprenoids are also found in plants with different chain lengths. The distribution of polyisoprenoid compounds (dolichol and polyprenol) was found in the leaf and stem tissues of Pinus merkusii strains derived from Aceh, Tapanuli and Kerinci. The extracted samples were analyzed by the two-dimensional thin-layer chromatography (2D-TLC) method. The distribution of dolichol and polyprenol compounds on the stems and leaves of Aceh, Tapanuli and Kerinci pines provided a type II categorization, both dolichol and polyprenol were traced in pine tissues. Total lipids in stem tissue ranged from 564.4-58.9 mg/g dw, polyisoprenoid values ranged from 1.34-2.44 mg/g dw. In the leaves, total lipids ranged from 590 to 669.43 mg/g dw while polyisoprenoid values ranged from 1.29 to 5.70 mg/g dw. The dolichol carbon chain length in the Pine stem of strain composed C70-C90, C65-C90, and C65-C95. Meanwhile, carbon chain-length of C85-C105, C70-C95, and C50-C65 were found in leaf tissues. The length of the polyprenol carbon chain in the stem was C60-C90, C50-C90, and C70-C90 respectively, while the chain lengths on the leaves were C60-C115, C50-C95, and C30-C90. The present study suggested the presence of both dolichol and polyprenols in Pinus merkusii without predomination either dolichol or polyprenol.